Interaksi Kebudayaan antara Persia dan Arab-Islam - M. Yakub (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
Cultural interaction between Persia and Islam occurred through nimerous ways, such as expansion process,(expansion of region by way of invasion). Through this process, Persia enriched the di-versity of Arabic-Islam cultures wich can be seen among others in implementation of administration of state intitutions (wizarah) wich was unique feature of Persia during the time when Abbasid Dynasty was in reign. Relocation of Abbasid capital drom Damasqus to Baghdad and translation activities formed an intense acculturation among the two cultures wich resulted in the growth and advencement of sciences. this was incited by the development of Arabic language, both as a language of administration and languge of science.